Implementasi media audio visual berbasis game dengan teknik akrostik dalam pembelajaran menulis puisi kelas iv sekolah dasarImplementasi media audio visual berbasis game dengan teknik akrostik dalam pembelajaran menulis puisi kelas iv sekolah dasar - Fadilla Intan Nurlaili; Retno Winarni; Joko Daryanto (Universitas Sebelas Maret, 2022)
The purpose of this study was to describe the implementation of the use of game-based audio-visual media with acrostic techniques in learning poetry writing skills for class IV. The subjects of this study were classroom teachers and fourth grade students. The data collection techniques used were interviews with fourth grade teachers, observations during poetry writing lessons, and documentation studies regarding the syllabus, and lesson plans. The validity test technique used in this research is source triangulation and technique triangulation. The research got the results that the application of game media can be carried out well in learning poetry writing skills. This can be proven when the learning takes place the teacher has used the media through the features in the game, such as material features and assignment features. This feature is also used by teachers to evaluate students, so that with the media game it is able to facilitate teachers in assessing and can attract students' interest in learning. The media makes the learning atmosphere fun so that students can easily accept the information conveyed by the teacher about writing poetry.